Criminal Responsibility Of National Road Organizers For Traffic Accidents On The Pantura Road As Seen From The Theory Of Legal Certainty - Ibnu Susilo; Muhamad Gary Gagarin; Muhamad Abas (Dinasti Research, 2026)
This study examines the qualification of criminal liability of national road administrators for traffic accidents caused by road damage based on Article 273 of Law Number 22 of 2009 concerning Traffic and Road Transportation, as well as the problems of law enforcement in the Pantura Jatisari area from the perspective of legal certainty theory. This research employs a normative juridical method with statutory and conceptual approaches. The findings indicate that national road administrators may be held criminally liable if negligence in road maintenance is proven to cause traffic accidents. The elements include culpa (negligence), unlawful act, and causality between road damage and the accident. However, in practice, the enforcement of Article 273 still faces various obstacles, such as unclear division of authority between institutions, weak implementation of criminal sanctions, and difficulties in proving causality. These conditions result in the failure to achieve legal certainty in holding road administrators accountable. Therefore, regulatory strengthening, clarity of responsible subjects, and consistent law enforcement are necessary to ensure road user safety and to realize the principle of legal certainty in public infrastructure governance.